1977
DOI: 10.1246/cl.1977.1195
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Reactions of 3-Phenyl-2-Isoxazolines Fused With Cycloalkane Ring

Abstract: In order to clarify the initial stage of the photoexcitation of the rigid Ph–C=N–O system, the photochemistry of several 2-isoxazolines possessing fused cycloalkane ring has been investigated. Several photoproducts such as 2H-azirine, cyclic enamine aldehydes, bicyclic oxazolines were isolated, and a generalized pattern of the photoreaction which is initiated by the N–O bond fission is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For a hydrogen substituent pathway, a) dominated, while for other substituents, especially for electron‐accepting compounds (CO 2 Me, CN), fragmentation via pathway b) dominated . Under photolysis, pathway b) was preferred …”
Section: Transformations Of Small Ring Annelated Isoxazolidinesmentioning
confidence: 99%
See 1 more Smart Citation
“…For a hydrogen substituent pathway, a) dominated, while for other substituents, especially for electron‐accepting compounds (CO 2 Me, CN), fragmentation via pathway b) dominated . Under photolysis, pathway b) was preferred …”
Section: Transformations Of Small Ring Annelated Isoxazolidinesmentioning
confidence: 99%
“…with the similar transformation of cyclopropanes) and dihydropyrrole derivative 133 (Scheme ). The latter compound is proposed to be the product of a distal C−C bond fission of intermediate 131‐A …”
Section: Transformations Of Small Ring Annelated Isoxazolidinesmentioning
confidence: 99%
“…In our previous reports we have shown that the nonselective [1-71 photochemical rearrangement of isoxazolines can be made selective by introducing a moiety, stabilizing the primary formed diradical. The photolysis of such products leads exclusively to heterocyclic enaminoaldehydes[8-11l.Measuring the quantum yields of the transformation of 4-R-substituted 8-phenyl-3,6,10-trioxa-9-azabicyclo- [5,3,0]-8-decenes 1 and 2 to 2-R-6-phenyl-7-formyl-~,4,5,8-tetrahydro-l,3-dioxa-S-azocines 3, where R was methyl and phenyl, we have found different @ values for eso derivatives '2b,cand endo derivatives 1 b , e. We now wish to report an investigation of this rare phenomenon on a greater series of derivatives 1 and 2.…”
mentioning
confidence: 99%